2022
DOI: 10.1017/wsc.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of target-site resistance to ALS-inhibiting herbicides in Ammannia multiflora populations

Abstract: Ammannia multiflora Roxb. is a dominant broadleaf weed which is a serious problem in southern China rice fields, and ALS-inhibiting herbicides have been used for its control for a long time. Excessive reliance of ALS-inhibiting herbicides has led to herbicide resistance in A. multiflora. In this study, 10 A. multiflora populations from Jiangsu province of China were collected, and the resistance levels and target-site resistance mechanisms to ALS-inhibiting herbicides bensulfuron-methyl and penoxsulam were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In this study, we tested the DPPH radical scavenging activity of 184 plant extracts and identified three extracts (FBCC-EP858 from A. multiflora, FBCC-EP920 from A. coccinea, and FBCC-EP1014 from S. gracilistyla) that possessed powerful antioxidant activity. A. multiflora, A. coccinea, and S. gracilistyla are plants known for their traditional medicinal uses, and their antioxidant properties were previously unknown or not well-characterized [21,27]. We found that these extracts enhanced antioxidant activity both in vitro and in vivo by activating the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we tested the DPPH radical scavenging activity of 184 plant extracts and identified three extracts (FBCC-EP858 from A. multiflora, FBCC-EP920 from A. coccinea, and FBCC-EP1014 from S. gracilistyla) that possessed powerful antioxidant activity. A. multiflora, A. coccinea, and S. gracilistyla are plants known for their traditional medicinal uses, and their antioxidant properties were previously unknown or not well-characterized [21,27]. We found that these extracts enhanced antioxidant activity both in vitro and in vivo by activating the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Ammannia multiflora is a plant belonging family Lythraceae and is well-known as an annual dicot weedy plant in agricultural lands and plants inhabiting aquatic environmental systems [21]. According to studies over the years, it has been proven that A. multiflora contains medicinal properties as it has shown antihyperglycemic activity, antimalarial properties, and microbicidal properties [21][22][23][24][25]. Regarding the biochemical and phytochemical analysis, the studies have revealed that it is rich in flavonoids, which may contribute to antioxidant activity [26].…”
Section: Introductionmentioning
confidence: 99%
“…Tanigali et al [ 33 ] found that the resistant mutations exclusively occurred in ALS1 or 3 in M. vaginalis . In our previous study, amino acid mutations in ALS1 or 2 independently, or in both, were found in Ammannia multiflora [ 34 ]. The preference of resistant mutations may be related to gene expression levels, herbicide use, and weed species.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that ALS gene mutation or gene overexpression can lead to the resistance of weeds to ALS inhibitor herbicides, while the enhanced metabolic capacity mediated by cytochrome p450 oxidases can lead to the resistance of weeds to ALS inhibitor herbicides and herbicides with other action mechanisms [44][45][46][47][48][49]. We found that the population of cleavers in different regions of Jiangsu Province had obvious resistance to the ALS inhibitors such as tribenuron-methyl, bensulfuron-methyl and halosulfuronmethyl, but was sensitive to the auxin herbicides and PPO inhibitors.…”
Section: Discussionmentioning
confidence: 99%